Tarmių fonetinių ypatybių atspindžiai „Sakytinės lietuvių kalbos tekstyne“ - Kačiuškienė, Genovaitė (Baltistica, 2012)
REFLECTIONS OF PHONETIC PECULIARITIES OF DIALECTS IN THE CORPUS OF THE SPOKEN LITHUANIAN LANGUAGE Summary According to the material of the “Corpus of the Spoken Lithuanian Language” (http://donelaitis.vdu.lt/ andrius/SKT5/5SKT-paiesk.php), dialectal phonetic forms marked as @d in the corpus are analysed. The most frequent dialectal forms recorded in the areas of academic communication, news media communication, private communication by telephone, private direct communication, semi-public direct communication and semi-public communication by telephone are discussed. The following conclusions based on the material under analysis are drawn: 1. 1,227 words of the total of 226,174 words used in the corpus have dialectal forms. It makes up 0.54% of all recorded words. 2. Dialectal forms used in the corpus of spontaneous language are 20 times more frequent than in the specially prepared language corpus (1.01% and 0.05% respectively). 3. The highest percentage of dialectal forms is used when speaking privately on the telephone (2,27%) or during direct private conversations (1,16%) when the infor-mant is not limited either by the environment or by the rules of standard Lithuanian. 4. The majority of dialectal forms are related to a certain shortening of word’s end – over 68 per cent of such cases were found. 5. The Lowland dialect predominates there; it is characterised by the diphthongisation of vowels o, ė, change of diphthongs ie, uo, retention of the ancient *an in end syllables. Phonetic peculiarities of Highland Lithuanian in the corpus are reflected quite poorly and are mostly related to the shortening of word’s end. 6. Various changes of sounds are peculiar to the spoken language of the corpus infor-mants: contraction and elision, syncope, apocope of word’s beginning.